The Keepers of the School: In harm's way - Clements, Andrew, 1949-2019.; Stower, Adam (New York : Atheneum Books for Young Readers, 2013)
As Benjamin Pratt and his friends Jill and Robert continue their efforts to save their school, they find themselves dodging two evil janitors, Lyman and Wally, but their team has also grown and now has a secret fund of millions of dollars.
Keywords: Schools -- Juvenile fiction; Janitors -- Juvenile fiction; Sailing -- Juvenile fiction; Families -- Massachusetts -- Juvenile fiction; Massachusetts -- Juvenile fiction